Levels of physical activity among students of Human Medicine at a university in northern Peru during the COVID-19 pandemic - Villarreal-Suyon, Beatriz Helena (2024)
Objective: To identify the levels of physical activity among students of Human Medicine at a university in northern Peru during the COVID-19 pandemic. Materials and methods: An observational, descriptive study conducted on 254 first- to fifth-year students of Human Medicine who were administered the International Physical Activity Questionnaire Short Form (IPAQ-SF) in 2021. Results: A total of 48.03 % of the students had a moderate level of physical activity. The sociodemographic characteristics most commonly observed were the female sex in the light (64.56 %) and vigorous (59.26 %) levels of physical activity and the male sex in the moderate (55.37 %) level of physical activity. Concerning the age, the youth stage predominated in all levels (light: 58.44 %, moderate: 62.60 % and vigorous: 61.11 %), contrary to the young adult stage, where all levels obtained the lowest percentage. According to the year of study, second-year students stood out in the light (36.71 %), moderate (36.07 %) and vigorous (58.49 %) levels, in contrast to fourth-year students, who achieved the lowest percentage in all levels (light: 3.8 %, moderate: 26.23 % and vigorous: 3.77 %). Finally, regarding the light level of physical activity, the mean number of hours sitting per day was 7.88 compared to the vigorous level, which attained a mean of 3.23. Conclusions: Most of the students of Human Medicine at a university in northern Peru had a moderate level of physical activity during the COVID-19 pandemic in 2021. The most prevailing sociodemographic characteristic was the female sex with a light level; those in the youth stage and the second year of studies showed all levels of physical activity. Moreover, students with a light level of physical activity remained more hours seated compared to the other levels.